Wrinkling of twisted thin films. (1st February 2023) - Wang, Fan-Fan; Wang, Ting; Zhang, Xiaoliang; Huang, Yangchao; Giorgio, Ivan; Xu, Fan
Abstract: Thin films usually exhibit instabilities and yield intricate wrinkles when two clamped ends are twisted. Here, we explore the wrinkling behavior and pitch-fork bifurcation of twisted thin films experimentally and theoretically. To quantitatively predict the post-buckling evolution of twist-induced wrinkling morphology, we develop a refined finite-strain plate model derived from 3D field equations and then solve it by using the finite element method with COMSOL. We examine the effects of aspect ratios and pre-tension on the wrinkling profile. We reveal three distinguished wrinkling evolution regimes depending on the aspect ratios of thin films as the twisting angle increases: (a) wrinkles initially occur at both free ends of the film and then develop toward the center; (b) wrinkles appear at the center and then develop toward both free ends; (c) wrinkles emerge at the center and are localized therein. The increase of film thickness and pre-stretch can strengthen the film stiffness and thus increase the critical twisting threshold, resulting in the prevention of wrinkle formation. Understanding the morphological pattern evolution of twisted films may guide rational designs of wrinkle-tunable membrane surfaces and structures. Highlights: We have experimentally and theoretically explored torsion-induced wrinkling pattern formation and evolution of soft thin films. We have uncovered three distinguished wrinkling evolution regimes depending on the aspect ratios of thin films. We have developed a refined finite-strain plate model to predict pattern selection. The increase of film thickness and pre-stretch can increase the critical twisting threshold, resulting in the prevention of wrinkle formation. Understanding the morphological pattern evolution of twisted films may guide rational designs of wrinkle-tunable membrane surfaces and structures.